Review of eastern Asian species of the mysid genus Rhopalophthalmus Illig, 1906 (Crustacea, Mysida) with descriptions of three new species - Hanamura, Yukio; Murano, Masaaki; Man, Alias (Zootaxa, 2011)
Mysid crustaceans of the genus Rhopalophthalmus Illig, 1906 (Crustacea: Mysida) are distributed in the eastern Atlantic through the Indo-West Pacific. In this paper, species of Rhopalophthalmus recorded from eastern Asian waters are reviewed on the basis of materials collected from south-eastern Asia to Japanese water. The taxonomic analysis led to the recognition of six species from the region, including three new species. Rhopalophthalmus phyllodus Murano, 1988 was regarded as a junior synonym of R. egregius Hansen, 1910. The identity of R. macropsis Pillai, 1964 has been controversial, and in this study, we recognised it as valid. However, specimens with remarkably stout and few spinose setae on the telson, often reported as either R. macropsis or R. longipes Ii, 1964 were determined to be a new species, R. armiger. In addition, two new species, R. hastatus and R. philippinensis, were reported from south-eastern Asian waters. A key to the 25 currently recognised world species is provided.